Time to Talk: A Review of Reading Girls: The Lives and Literacies of Adolescents - Erica Newhouse (Networks: An Online Journal for Teacher Research, 2015)
Hadar Dubowsky Ma’ayan regards Reading Girls: The Lives and Literacies of Adolescents as an important extension of Finder’s (1997) Just Girls: Hidden Literacies and Life in Junior High. Ma’ayan, a 5th grade teacher, conducts practitioner action research while taking a year off from teaching at Lincoln Middle School. Once a week, she met with a group of six racially and socioeconomically diverse 8th grade girls to participate in a Girls’ Literacy Discussion Group (GLDG).